Plutarco. Vidas Paralelas - Alexandre e César - Maria de Fátima Silva (Classica Digitalia: Autores Gregos e Latinos: textos, 2019)
Plutarch distinguishes Alexander king of Macedonia as a genius in military art and diplomacy to consolidate his power. During his life, just a little more than 30 years, the young king changed the political and cultural map of his time: he put a large European, African, and Asiatic space under his authority, promoted an intercultural globalisation to unify a multiplicity of peoples as a huge empire, and transferred the intellectual centre of the world from Athens to other oriental cities. But an unmeasured ambition harmed all his project and even its author's life. By pairing Caesar with Alexander, Plutarch brings out the fame of a great conqueror, the aspect of personality that the biographer most admires in this Roman statesman. But the ambition (philotimia) that repeatedly moves Caesar represents the black side that will lead him to the death, before he can reap the fruits of his eagerness. Although not completely transforming Caesar into a cruel tyrant (which he was not), this Life illustrates, however, a criticism of the exacerbated and irrational ambition of power.